PENGETAHUAN DAN SIKAP PERAWATAN PAYUDARA DENGAN PRODUKSI ASI IBU NIFAS - Zumaro, Elqy Mei (Jurnal Ilmiah Kebidanan Imelda, 2023)
Lack of calories and protein in toddlers, toddlers and young children is a nutritional problem that is currently the biggest problem in Indonesia. The most common nutritional problem in infancy is due to a lack of intake of Mother's Milk (ASI). Based on the results of the initial interview, 6 out of 10 postpartum women respondents who were interviewed did not know how to care for the breast, the benefits of breasts and during the postpartum period there were problems experienced, namely the nipples were not protruding/immersed so that the milk did not come out and after a few days it just came out. The purpose of this study was to find out whether knowledge and attitudes in breast care affect milk production in postpartum mothers. The design and type of this research is cross-sectional analytic. The population in this study were all postpartum mothers who visited the Bojong Community Health Center, Tegal Regency. Acidental sampling was used as a technique for sampling, namely the number of samples used was 30 respondents. Primary data obtained from filling out the questionnaire. The Chi Square test was used to analyze the bivariates in this study.Analysis of the results of the study obtained a p-value of 0.002, which indicates that knowledge and attitudes of breast care in postpartum mothers have an effect on milk production.